2014
DOI: 10.1016/j.jacc.2014.06.1177
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Frequency of Atrial and Ventricular Ectopic Beats and Biventricular Pacing Percentage and Outcomes in Patients With Cardiac Resynchronization Therapy

Abstract: Relatively low frequencies of ectopic beats (≥0.1%) dramatically increase the probability of low biventricular pacing (<97%), with reduced CRT efficacy by less reverse remodeling and higher risk of HF/death and VTA. This supports pre-implantation Holter monitoring of patients selected for CRT for optimal outcome. (MADIT-CRT: Multicenter Automatic Defibrillator Implantation With Cardiac Resynchronization Therapy; NCT00180271).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…PVCs account for 16.6% of the loss of CRT 3 . An association between the frequency of PVCs and outcome in patients with CRT has been demonstrated 4 . Successful ablation of PVCs promotes reverse remodeling in CRT nonresponders 5 …”
Section: Discussionmentioning
confidence: 99%
“…PVCs account for 16.6% of the loss of CRT 3 . An association between the frequency of PVCs and outcome in patients with CRT has been demonstrated 4 . Successful ablation of PVCs promotes reverse remodeling in CRT nonresponders 5 …”
Section: Discussionmentioning
confidence: 99%
“…Another interesting study by Ruwald et al. demonstrated that even the presence of ectopic beats in CRT patients is significantly associated with poor outcome in terms of subsequent ventricular arrhythmias, heart failure and death …”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Apart from lead localisation, achievement of an almost 100% biventricular pacing rate is a major concern to derive benefit from CRT devices. 32,33 The clinical conditions that impair high pacing rates, such as atrial fibrillation and ventricular ectopic beats should be routinely searched and treated during the followup of CRT recipients. 32,33 Appropriate device programming regarding the atrioventricular (AV) and interventricular (VV) intervals is essential to achieve optimal diastolic filling and stroke volume that is associated with favourable outcomes after CRT.…”
Section: Echocardiogram-based Device Optimisationmentioning
confidence: 99%
“…32,33 The clinical conditions that impair high pacing rates, such as atrial fibrillation and ventricular ectopic beats should be routinely searched and treated during the followup of CRT recipients. 32,33 Appropriate device programming regarding the atrioventricular (AV) and interventricular (VV) intervals is essential to achieve optimal diastolic filling and stroke volume that is associated with favourable outcomes after CRT. [34][35][36] All of the above-mentioned optimisation steps are known to affect the paced QRSd following device implantation.…”
Section: Echocardiogram-based Device Optimisationmentioning
confidence: 99%